REVIEW FOR THE GENERALIST: EVALUATION OF PEDIATRIC FOOT AND ANKLE PAIN - Kristin M. Houghton (Amaltea Medical Publishing House, 2009)
Foot and ankle pain is common in children and adolescents. Problems are usually related to skeletal maturity and are fairly specific to the age of the child. Evaluation and management is challenging and requires a thorough history and physical exam, and understanding of the pediatric skeleton. This article will review common causes of foot and ankle pain in the pediatric population.